2018
DOI: 10.18203/2320-1770.ijrcog20181012
|View full text |Cite
|
Sign up to set email alerts
|

Unscarred uterine rupture: a retrospective analysis in tertiary center

Abstract: Background: Uterine rupture is a catastrophic obstetrical emergency associated with a significant fetomaternal morbidity and mortality. Many risk factors for uterine rupture, as well as a wide range of clinical presentations have been identified. The objectives of the present study were to analyze the frequency, predisposing factors, maternal and fetal outcomes of unscarred uterine rupture.Methods: A retrospective analysis of cases of unscarred uterine rupture was conducted at the Department of Obstetrics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
0
1
Order By: Relevance
“…It is reported that the uterus of multiparas is fragile. 12 In contrast to the literature, present study showed a rate of 22.86% uterine ruptures occurring in primiparous women, that is to say 6 per 10,000 deliveries, of which three cases were objectified as contracted pelvis. According to Sweeten and al., the prevalence in developed countries is 1 per 10,000 deliveries.…”
Section: Discussioncontrasting
confidence: 94%
“…It is reported that the uterus of multiparas is fragile. 12 In contrast to the literature, present study showed a rate of 22.86% uterine ruptures occurring in primiparous women, that is to say 6 per 10,000 deliveries, of which three cases were objectified as contracted pelvis. According to Sweeten and al., the prevalence in developed countries is 1 per 10,000 deliveries.…”
Section: Discussioncontrasting
confidence: 94%